Entrepreneurial orientation and performance of small and medium enterprises: Mediating effect of entrepreneurial competencies - Mukaram Ali Khan; Kashif Rathore; Muhammad Adnan Sial (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Small and Medium Enterprises (SMEs) play a vital role in the development of an economy. Looking at this perspective, it is imperative to develop the entrepreneurial orientation and to update the entrepreneurial competencies in order to perform in this competitive environment. This research study focusesspecifically on these aspects and attemptsto establish the need of identifying entrepreneurial orientationand entrepreneurial competenciesin entrepreneurs in order to enhance enterprise performance.Researchers have collected the data from SMEs in Pakistan using simple random sampling technique. Partial least square based structural equation modelingis used in order to analyze the data andtotest the hypotheses. Analysis revealed positive relationships between entrepreneurial orientationand entrepreneurial competencies, entrepreneurial competencies and entrepreneurial performance,entrepreneurial orientation and entrepreneurial performance. Moreover, entrepreneurial competency has proved to be a mediatorbetween entrepreneurial orientation and entrepreneurial performance. Resource based view explains the importance of entrepreneurs as competent resources in playing vital role in escalating the performance level of SMEs. Lastly, this study can be used by different stakeholders to emphasize more on developing the competency level of entrepreneurs and determining the level of orientation towards better performance of enterprises.
Keywords: 330; SMEs; entrepreneurial orientation; entrepreneurial competencies; enterprise performance; creativity; autonomy; risk taking propensity; innovativeness